#### Answer

$y = \frac{9}{4}x^{\frac{5}{4}} -2e^{-2x}$

#### Work Step by Step

$y = x^{\frac{9}{4}}+ e^{-2x}$
$y = \frac{9}{4}x^{\frac{5}{4}} -2e^{-2x}$

Published by
Pearson

ISBN 10:
0321999584

ISBN 13:
978-0-32199-958-0

$y = \frac{9}{4}x^{\frac{5}{4}} -2e^{-2x}$

$y = x^{\frac{9}{4}}+ e^{-2x}$
$y = \frac{9}{4}x^{\frac{5}{4}} -2e^{-2x}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.